Non-spore-forming thermoduric bacteria vary considerably in thermal resistance in milk media between strains from the same genus - Caroline Motzer; Martin Wiedmann; Nicole Martin (Journal of Dairy Science)
ABSTRACT: Thermoduric bacteria, defined as those that survive temperatures considerably above their maximum growth temperature, are enumerated in milk using the laboratory pasteurization count (LPC) test. This test selects for bacteria that show limited cell count reductions under vat pasteurization conditions (i.e., 63°C for 30 min); however, this test has limitations. One limitation of the LPC is that the test selects for a broad group of thermoduric bacteria, many of which are not reported to survive HTST pasteurization, the most commonly used pasteurization method in the United States. There are 2 distinct groups of thermoduric bacteria that can affect milk quality if implicated in finished product: spore-forming and non-spore-forming. Contemporary studies have primarily focused on spore-forming bacteria, leaving a gap in research regarding non-spore-forming thermoduric bacteria. Therefore, the goals of this study were to (1) assemble a set of non-spore-forming thermoduric bacteria previously isolated from heat-treated dairy matrices and (2) use that set to identify one or more laboratory enumeration method(s) that select for thermoduric bacteria relevant to contemporary HTST-treated dairy products. To that end, a set of 38 isolates of non-spore-forming thermoduric bacteria were inoculated into skim milk broth and independently subjected to 4 different heat treatments (A: 63°C for 30 min, B: 65°C for 15 min, C: 68°C for 7 min, and D: 70°C for 5 min), followed by plating using 2 different media types (standard methods agar [SMA] and aerobic count Petrifilms [AC Petrifilms; Neogen, Lansing, MI]), each of which were incubated at 32°C and enumerated after 3 different incubation periods (24, 48, and 72 h). Results from each unique method were compared with the standard method (i.e., LPC test). Results indicate that AC Petrifilms overestimate cell count reductions for some genera, suggesting that AC Petrifilm may not be an appropriate medium for enumerating these genera. Heat treatment D (i.e., 70°C for 5 min) showed a trend for higher reduction in cell counts compared with heat treatment A (i.e., standard method) and 48 h incubation allowed enough time for bacterial recovery. Therefore, we propose the evaluation of heat treatment D (i.e., 70°C for 5 min), followed by plating with SMA and incubation of 48h at 32°C in future studies of naturally contaminated milk. Our results also suggest that there is considerable variability in thermal resistance among isolates of the same genus. These phenotypic differences may be driven by yet unknown genotypic features that should be further examined. Ultimately, this study provides an update to the existing knowledge of non-spore-forming thermoduric bacteria and future studies should focus on evaluating non-spore-forming thermoduric bacteria in naturally contaminated dairy products.